Multi-center evaluation of the fully automated PCR-based Idylla™ KRAS mutation assay for rapid KRAS mutation status determination on formalin-fixed paraffin-embedded tissue of human colorectal cancer - Solassol, J; Vendrell, J; Märkl, B; Haas, C; Bellosillo, B; Montagut, C; Smith, M; O'Sullivan, B; D'Haene, N; Le Mercier, M; Grauslund, M; Melchior, L; et al. (Public Library of Science, 2016)
Since the advent of monoclonal antibodies against epidermal growth factor receptor (EGFR) in colorectal cancer therapy, the determination of RAS mutational status is needed for therapeutic decision-making. Most prevalent in colorectal cancer are KRAS exon 2 mutations (40% prevalence); lower prevalence is observed for KRAS exon 3 and 4 mutations (6%) and NRASexon 2, 3, and 4 mutations (5%). The Idylla™ KRAS Mutation Test on the molecular diagnostics Idylla™ platform is a simple (<2 minutes hands-on time), highly reliable, and rapid (approximately 2 hours turnaround time) in vitro diagnostic sample-to-result solution. This test enables qualitative detection of 21 mutations in codons 12, 13, 59, 61, 117, and 146 of the KRAS oncogene being clinically relevant according to the latest clinical guidelines. Here, the performance of the Idylla™ KRAS Mutation Assay, for Research Use Only, was assessed on archived formalin-fixed paraffin-embedded (FFPE) tissue sections by comparing its results with the results previously obtained by routine reference approaches for KRAS genotyping. In case of discordance, samples were assessed further by additional methods. Among the 374 colorectal cancer FFPE samples tested, the overall concordance between the Idylla™ KRAS Mutation Assay and the confirmed reference routine test results was found to be 98.9%. The Idylla™ KRAS Mutation Assay enabled detection of 5 additional KRAS-mutated samples not detected previously with reference methods. As conclusion the Idylla™ KRAS Mutation Test can be applied as routine tool in any clinical setting, without needing molecular infrastructure or expertise, to guide the personalized treatment of colorectal cancer patients.